Volume 3: Joint MSEC-NAMRC Symposia 2016
DOI: 10.1115/msec2016-8784
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Based Geometric Compensation for Thermal Deformation in Additive Manufacturing Processes

Abstract: Additive manufacturing (AM) processes involve the fabrication of parts in a layer-wise manner. The layers of material are deposited using a variety of established methodologies, the most popular of which involve either the use of a powerful laser to sinter/melt successive layers of metal/alloy/polymer powders or, the deposition of layers of polymers through a heated extrusion head at a controlled rate. The thermal nature of these processes causes the development of temperature gradients throughout the part and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The study further showed that there is a weak correlation between the aforementioned process parameters and the porosity of a printed part. Additionally, Chowdhury 77 demonstrated the use of a feedforward NN for compensating for dimensional inaccuracies in printed parts caused by residual stresses. Given a part to be printed, the NN is first trained on the predicted post-print deformation of the part, which is obtained through thermomechanical simulations ( Figure 3D).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study further showed that there is a weak correlation between the aforementioned process parameters and the porosity of a printed part. Additionally, Chowdhury 77 demonstrated the use of a feedforward NN for compensating for dimensional inaccuracies in printed parts caused by residual stresses. Given a part to be printed, the NN is first trained on the predicted post-print deformation of the part, which is obtained through thermomechanical simulations ( Figure 3D).…”
Section: Reviewmentioning
confidence: 99%
“…Algorithm-based methods, especially ML, provide several benefits and advantages in different types of AM processes as so far discussed. However, there remain challenges, giving rise to future opportunities in the development of the three AM 20 SVM, 83 NNs, 84 Material design decision trees, 33 CNNs 34 Process parameter determination PCA, 85 NNs 77,86 Defects detection clustering, 10 (1) Refined interface settings for TO: TO of multi-scale or multi-material frameworks in general does not take into consideration practical limitations at phase transition boundaries. Namely, the interfaces are assumed to be strong and have an abrupt material change, which is not the case for many AM technologies.…”
Section: Challenges and Perspectivementioning
confidence: 99%
“…The utilization of deep learning, and specifically autoencoders, also led to the creation of a computational framework that models the curiosity of a given user in order to provide surprising examples [21]. Neural networks have also been utilized to automatically predict quality defects in automotive parts [22] and to support design for additive manufacturing [23][24][25]. These examples, while not exhaustive, serve to highlight potential utility of neural networks for design and the need for a standardized approach to implementing them.…”
Section: Neural Network and Deep Learningmentioning
confidence: 99%
“…Rudimentary neural networks have been used to support DfAM in several ways, including estimation of build time [29], prediction of bead geometry for weld-based rapid prototyping [30], and compensation for thermal deformation [31]. In most cases, these and other AM-related neural networks primarily serve to approximate time-consuming calculations that directly connect the "as-designed" structure to the "as-manufactured" structure.…”
Section: Machine Learning To Predict Am Qualitymentioning
confidence: 99%